Influence of composition and precipitation evolution on damage at grain boundaries in a crept polycrystalline Ni-based superalloy. (March 2019) - Kontis, Paraskevas; Kostka, Aleksander; Raabe, Dierk; Gault, Baptiste
Abstract: The microstructural and compositional evolution of intergranular carbides and borides prior to and after creep deformation at 850 °C in a polycrystalline nickel-based superalloy was studied. Primary MC carbides, enveloped within intergranular γ′ layers, decomposed resulting in the formation of layers of the undesirable η phase. These layers have a composition corresponding to Ni3 Ta as measured by atom probe tomography and their structure is consistent with the D024 hexagonal structure as revealed by transmission electron microscopy. Electron backscattered diffraction reveals that they assume various misorientations with regard to the adjacent grains. As a consequence, these layers act as brittle recrystallized zones and crack initiation sites. The composition of the MC carbides after creep was altered substantially, with the Ta content decreasing and the Hf and Zr contents increasing, suggesting a beneficial effect of Hf and Zr additions on the stability of MC carbides. By contrast, M5 B3 borides were found to be microstructurally stable after creep and without substantial compositional changes. Borides at 850 °C were found to coarsen, resulting in some cases into γ′- depleted zones, where, however, no cracks were observed. The major consequences of secondary phases on the microstructural stability of superalloys during the design of new polycrystalline superalloys are discussed. Graphical abstract: Image 1